Effect of Stress on Visual Functions - Syed Hamza Ali, Muhammad Jamshed, Syeda Rushda Zaidi, Samia Iqbal, Hakim Anjum Nadeem (Pakistan Journal of Ophthalmology, 2017)
Objective:This study focuses to find verification on the visual functions due to sound, effects of stress, anxiety or depressions and furthermore, to evaluateoverall visual performance in patients dealing with stress and with no other ocular anomalies. To find that which component of visual system is compromised due to stress level. Study Design: Cross-sectional study Duration and Place of Study: February to May 2017 Department of psychology, Fountain house, Lahore, Pakistan. Department of Optometry and Vision Sciences, The University of Lahore, Lahore, Pakistan. Method:Visual acuity screening, Glare sensitivity, Contrast sensitivity, Color vision and Visual field were performed on sample of 70 patients having stress using Ishihara test, Snellen chart, pelli robson low contrast test, Snellen chart for Glare sensitivity and Confrontation method respectively. Screening tests were carriedto measure visual functions in patients with diagnosed stress disorders. Patients diagnosed of stress within the age range of 18-40 years were taken into consideration. Data is quantified using the help of SPSS 20. Results: 47.1% shows defect in Contrast sensitivity and42.85% of stress patients show decrease in Visual acuity 35.7% subject shows decrease in glare sensitivity while 99% of patients exhibit no defect in visual field and color vision. The study conducted is unbiased to age, occupation and gender. Conclusion:Stress affects the visual functions. Visual acuity, glare sensitivity and contrast sensitivityare affected by stress in majority cases. However,stress patients have normal color vision and visual field. KEY WORD:Stress,visual acuity, visual field, contrast sensitivity, color vision.